Evaluation of integrated sludge worm and catfish farming with biofloc system - Pardiansyah, Dedi; Supriyono, Eddy; Djokosetianto, Daniel (Indonesian Society of Scientific Aquaculture (ISSA), 2014)
ABSTRACTCurrently, supply of sludge worm (Tubifex sp.) merely came from wild, so that it could not meet demand for fish hatchery. Additionally, harvest from the wild did not have a quality assurance, due to the possibility of sludge worm becoming an agent of disease. This study was conducted to evaluate the production of sludge worm culture by utilizing catfish culture waste (Clarias sp. ) in bioflok system. In this system, water from catfish culture media flowed into sludge worm culture media using recirculation systems. This study used a completely randomized design with four treatments and two replications, in which treatment A (addition of catfish culture waste from intensive system), treatment B (addition of catfish culture waste from biofloc system), treatment C (the addition of fermented chicken manure at the beginning of experiment as negative control), and treatment D (addition of fermented chicken manure at the beginning of experiment and then every five days as positive control). The results showed that the highest production was obtained by treatment B at biomass growth of 0.97 kg/m2 and sludge worm density of 388.000 individu/m2. Keywords: sludge worm, biofloc, chicken manure, catfish, catfish culture waste ABSTRAK Saat ini pasokan cacing sutra (Tubifex sp.) hanya berasal dari alam, sehingga belum mencukupi permintaan untuk kegiatan pembenihan ikan. Selain itu, hasil tangkapan dari alam tidak memiliki jaminan kualitas, karena cacing sutra dapat menjadi agen penyakit. Penelitian ini dilakukan untuk mengevaluasi hasil produksi budidaya cacing sutra dengan memanfaatkan limbah budidaya ikan lele (Clarias sp.) sistem bioflok. Pada sistem ini, air dari media budidaya ikan lele dialirkan ke media pemeliharaan cacing sutra menggunakan sistem resirkulasi. Penelitian ini menggunakan rancangan acak lengkap dengan empat perlakuan dan dua ulangan, yaitu perlakuan A (pemberian limbah ikan lele sistem intensif), perlakuan B (pemberian limbah ikan lele sistem bioflok), perlakuan C (penambahan fermentasi kotoran ayam pada awal penelitian sebagai kontrol negatif), serta perlakuan D (penambahan fermentasi kotoran ayam pada awal penelitian yang dilanjutkan setiap lima hari sekali sebagai kontrol positif). Hasil penelitian menunjukkan bahwa produksi cacing sutra tertinggi diperoleh pada perlakuan B dengan pertumbuhan bobot sebesar 0,97 kg/m2 dan kepadatan cacing sutra sebesar 388.000 individu/m2. Kata kunci : cacing sutra, bioflok, kotoran ayam, ikan lele, limbah budidaya ikan lele